The effect of variable chain length on the electronic properties of electroluminescent polymers - Almeida, A. M. (2001)
We have used self-consistent molecular dynamics calculations with semi-empirical quantum chemistry at the complete neglect of differential overlap (CNDO) level to discuss some of the issues relating to the electronic processes involved in electroluminescence of a particular conjugated polymer: poly(p-phenylene-vinylene) (PPV). Specifically addressed are the effects of chain length and molecular charge on the electronic properties of individual PPV strands, such as chemical potential, charge induced defects and charge rearrangement among the polymer atoms. The effect of high electric fields on charge-induced defects already formed is also discussed.